Performance assessment and player's monitoring in soccer - Silva, Rui Miguel Fernandes Pereira da (2021)
The relentless search for the best performance (physical, technical, tactical and psychological) in the field, force coaches, athletes and other surrounding departments to interact in a harmonious way. The aim is to adjust and direct the training through periodic and continuous evaluations that will facilitate decision making. This internship report belongs to the master course in Sports Training from the Superior School of Sports and Leisure, with the objective of obtaining a Master's degree. Taking into account the chosen specialization (soccer), this internship was carried out in the high-performance department (DAR) assigned to “B” team of Vitória Sport Clube, in Guimarães. The objectives of this internship were to: (i) support the DAR in the periodic and continuous assessments; (ii) support the return-to-play process of injured athletes; (iii) propose the creation of a periodic and continuous assessment process, from the U13 to “A” team; (iv) propose the creation of the club’s research laboratory, and (v) to produce and publish two scientific papers related with periodic and continuous assessments. All the objectives initially proposed were fully accomplished. In fact, my expectations regarding both the master course and this internship were completely exceeded. Two scientific papers were published. The paper 1 aimed to assess changes in physical fitness of amateur soccer players after a pre-season training period. Results revealed a lack of significant positive changes after the assessed period. The paper 2 aimed to test the relationship of volume and weekly training intensities with match-running demands of professional male soccer players. Results revealed that weekly training volume and intensity of high-intensity demands had moderate relationships with match high-intensity demands. For all the above-mentioned, this internship drew a robust profile in me in order to combine science with practice, and to transmit this path to all stakeholders involved in this process of “order-versus-disorder” soccer context.